La politica europea di prossimità: aspetti economici e politici. - Vaccaro, Mauro (Rivista di studi politici internazionali, 2007)
Since the big 2004 enlargement, the European Neighbourhood Policy has aimed to construct a « ring of friends » around European Union’s borders, and establish close and privileged relationship with the new neighbouring Countries that do not have an EU membership perspective in the short run. This paper tries to clarify the main problems and real potentials related to this new initiative, focusing in particular on the political and economic aspects. The European Neighbourhood Policy comprehensively covers a large, changing and strategically complex area, where Europe aims to play a bigger role, while having to face such other actors’ similar ambitions, as Russia. In this framework, if the EU is able to offer greater economic incentives, the ENP could become an efficient instrument of « europeanisation » in the sense of political, economic and societal transformation of neighbouring States; otherwise it will be seen as a second-class alternative to the EU membership and a weak mechanism to mitigate the negative effects of the enlargement on the neighbouring Countries. RÉSUMÉ - Après le grand élargissement de 2004, la politique européenne de voisinage vise a créer un « cercle d’amis » autour de l’Union Européenne, en établissant des relations intenses et privilégiées avec les nouveaux Pays voisins qui n’ont pas la perspective d’entrer à court terme dans l’Union. Cet article essaye de mettre en évidence les faiblesses et les potentialités de cette nouvelle initiative, en soulignant en particulier les aspects politiques et économiques. La politique de voisinage s’inscrit dans une région très vaste et en évolution, dans laquelle l’Europe voudrait jouer un rôle plus important mais doit aussi faire face aux ambitions d’autres acteurs comme la Russie. Dans ce contexte, si les incitants économiques de l’Europe seront intéressants pour les Pays tiers, alors la politique de voisinage pourra représenter un puissant instrument de « européanisation » pour le voisinage; sinon, elle sera entendue comme une alternative de deuxième catégorie par rapport à l’entrée dans l’Union, et restera seulement un faible mécanisme pour limiter les effets négatifs de l’élargissement sur les Pays voisins.